Rethinking the gendering of agency in male suicide: more-than-human connections in violence against the self - Jaworski, Katrina (Interconnecting the violences of men, 2025)
In contemporary Western contexts, suicide is often understood as an explicitly individual choice and act. This understanding has been advanced by an anthropocentric perspective, which sees suicide as a thoroughly human phenomenon. But what if the exercise of agency in suicide is more than human? In response, this chapter examines the gendering of male suicide as an important site for understanding the socio-cultural constitution of suicide. I begin by discussing traditional and more progressive ways of understanding male suicide. Drawing on elements of Judith Butler’s and Karen Barad’s philosophical work, I then theorise male suicide as performative by analysing selected scenes from the Hollywood films, Leaving Las Vegas, Monster’s Ball and A Star is Born, with each film representing a different method of suicide. In so doing, I unpack the way human and non-human agencies engender violence in male representations of suicide. Throughout the chapter, I argue that agency in male suicide is more than human because that which is human depends on non-human materiality. I also argue that non-human materiality offers new possibilities for challenging hegemonic and, by extension, masculinist interpretations of male self-destruction and violence against others.